Direct Methanation and Storage Concepts for the Flexibilization of Biogas Plants. Issue 3 (22nd December 2022) - Flach, Charley; Conti, Fosca; Bayraktar, Ahmet; Goldbrunner, Markus
Abstract: Enrichment of the methane fraction in a biogas mixture is an innovative possibility to make existing biogas plants more flexible by using excess power. In the described concept, the CO2 in the biogas is directly catalytically converted into CH4 with H2 . The CH4 ‐enriched biogas is again fed into the digester to save energy for later use in the combined heat‐and‐power unit. Additionally, the fed heat gas can mix and heat the substrate. A heat pipe injector system was therefore developed for cooling the hot biogas stream after methanation and to prevent damage to the microbial consortia during the biomass mixing. The concept was proven at a laboratory‐scale biogas plant. Abstract : Enrichment of the methane fraction in a biogas mixture is a possibility, though challenging, to optimize the existing biogas plants by using excess power. The methanation process and the consequent heat release are studied in a laboratory biogas plant with an innovative heat pipe injector system for cooling the enriched biogas and remixing the biomass substrate.